Reconstruction of elbow flexion in arthrogryposis multiplex congenita type I: results of transfer of pectoralis major muscle with follow-up at skeletal maturity - Chomiak, Jiří; Dungl, Pavel; Včelák, Josef (Journal of pediatric orthopedics, 2014)
BACKGROUND: The purpose of this study was to analyze the results of a pectoralis major transfer to restore active elbow flexion in patients with extension elbow contracture in arthrogryposis. The hypotheses were: (1) this transfer ensures permanent useful elbow flexion; and (2) flexion elbow deformity will not progress during growth and after its cessation. METHODS: Unipolar transfer of the 3 distal parts of the pectoralis major muscle was used in 9 extremities of 5 patients (age range, 5 to 9 y; average age, 6.3 y) and the results were prospectively followed in the period of 13 to 16 years. Posterior elbow release was necessary in 5 extremities to achieve passive flexion of 90 degrees before the transfer. The subjective evaluation of daily living activities and data on the physical examination of the range of movement of the elbow, muscle strength, and electrical activity of the transferred muscle were assessed. Two specimens from transferred muscles were histologically examined. RESULTS: All extremities achieved the active elbow flexion. Significant improvement of function for daily living activities was achieved in 5 extremities (55.5%). It includes the following results: 1 very good with flexion of 90 degrees and a deficit of extension of 35 degrees; 2 good with flexion of 92 and 100 degrees and a lack of extension of 42 and 45 degrees; and 2 satisfactory with a limited arc of motion between 20 and 45 degrees. Four extremities remained unsatisfactory with the arc of motion of 5 to 15 degrees. Significant elbow flexion contracture of 70 to 80 degrees developed in 4 extremities. Extremities with a necessity of posterior elbow release achieved a limited range of movement or significant elbow flexion contracture. Electromyography corresponded to a partial denervation of the transferred muscle followed by reinervation. Histologic examinations showed partial atrophy with signs of ongoing regeneration. CONCLUSIONS: The hypotheses of the study were not confirmed, because this muscle transfer restores useful elbow flexion without flexion deformity if the passive flexion at children's age exceeds 90 degrees without a necessity of posterior release. In these cases, bilateral pectoralis to biceps transfer is recommended. LEVEL OF EVIDENCE: Level II.
Keywords: Contracture; Female; dítě; předškolní dítě; ženské pohlaví; Pectoralis Muscles; svalová síla; artrogrypóza; paže; kontraktura; lidé; Activities of Daily Living; následné studie; Muscle Strength; Electromyography; Range of Motion, Articular; loketní kloub; rozsah kloubních pohybů; činnosti denního života; prsní svaly; prospektivní studie; Follow-Up Studies; Male; Prospective Studies; Child, Preschool; Child; mužské pohlaví; Arthrogryposis; Arm; elektromyografie; Elbow Joint; Humans